Red spinach flour substitution in cookies: effects on iron content, antioxidant activity, and sensory acceptability for anemia prevention - Yeni Tutu Rohimah; Dwi Retna Prihati; Titik Lestari (International Journal of Public Health Science (IJPHS), 2026)
Iron deficiency anemia affects approximately 30% of Indonesian women of reproductive age, underscoring the urgent need for affordable, iron-rich food interventions. This study investigated the effect of red Amaranth (Amaranthus tricolor L.) flour substitution on iron content, antioxidant activity, and sensory acceptability of composite flour cookies. A completely randomized design was employed with five substitution levels (0%, 10%, 20%, 30%, and 40%), each with three replications, yielding 15 experimental units of cookie batches. Iron content was determined using atomic absorption spectrophotometry, antioxidant activity via the DPPH method, and sensory acceptability through hedonic testing by 30 semi-trained panelists. Results demonstrated that iron content increased significantly (p < 0.05) with higher substitution levels, while antioxidant activity improved from very weak to moderate categories. However, sensory acceptability declined significantly at substitution levels of 30% and above, particularly in color and taste attributes. The 20% substitution level emerged as the optimal formulation, achieving substantially elevated iron content contributing meaningfully toward the recommended dietary allowance per serving, enhanced antioxidant capacity, and maintained good sensory acceptability across all attributes. These findings suggest that red Amaranth-substituted cookies represent a feasible, community-level dietary strategy for complementing existing iron deficiency anemia prevention programs in Indonesia.